Hamlet's Arab Journey : Shakespeare's Prince and Nasser's Ghost. - Litvin, Margaret (Translation/transnation., 2011)
For the past five decades, Arab intellectuals have seen themselves in Shakespeare's Hamlet: their times "out of joint," their political hopes frustrated by a corrupt older generation. Hamlet's Arab Journey traces the uses of Hamlet in Arabic theatre and political rhetoric, and asks how Shakespeare's play developed into a musical with a happy ending in 1901 and grew to become the most obsessively quoted literary work in Arab politics today. Explaining the Arab Hamlet tradition, Margaret Litvin also illuminates the "to be or not to be" politics that have turned Shakespeare's tragedy into the ess.